The Myth of the Coder. - Bullynck, Maarten; De Mol, Liesbeth (Communications of the ACM, 2024)
This article explores the distinction between the role of a computer programmer compared to the role of the computer coder. First, the origin of the separation of these two roles in a report by Herman H. Goldstine and John von Neumann is discussed, followed by the its perpetuation in trade journals in the 1950s especially by article author Grace Murray Hopper.